KEMAMPUAN BERBAHASA ANAK USIA DINI DENGAN POLA ASUH DIBERI GADGET DAN NON-GADGET - Nurul Hidayati; Farida Nugrahani; Suwarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to 1) analyze and describe the language skills of early childhood with a parenting style provided with gadgets, and 2) analyze and describe the language skills of early childhood with a parenting style without gadgets. The type and approach used is qualitative with a case study approach. Data was obtained through observation and interviews as well as printed books and documentation. The data source comes from kindergarten or PAUD children in Karanganyar Regency. Data collection techniques through observation, documentation and interviews. Data analysis followed the Miles and Huberman method, collecting, presenting, reducing and drawing conclusions from samples selected using incidental sampling. The data validation technique uses triangulation techniques. The research results show that children who grow up with gadgets have limited linguistic abilities, especially in articulating emotions and making coherent statements, even though they can pronounce words clearly. Meanwhile, parenting children without gadgets also face difficulties in syntax, syntax and semantics, so they have difficulty forming coherent phrases and sentences and articulating their desires clearly.